Respuesta :
Answer:
5x³+10x²-3x+3
Step-by-step explanation:
(4x²-3x) - (-5x³-6x²-3)
5x³+10x²-3x+3
If equations M(x)=[tex]4x^{2} -3x[/tex] and N(x)=[tex]-5x^{3}-6x^{2} -3[/tex] then M(x)-N(x)=[tex]5x^{3} +10x^{2} -3x+3[/tex].
What is equation?
An equation is a relationship between two or more variables expressed in equal to form. It is often equated to find the values of variables. The form of an equation is ax+by=c.
How solve equations?
We have been given M(x)=[tex]4x^{2} -3x[/tex] and N(x)=[tex]-5x^{3}-6x^{2} -3[/tex] and we have to find the difference between M(x) and N(x) and to solve them we have to open the brackets and add the coefficients of variable.
M(x)-N(x)=[tex]4x^{2} -3x-(-5x^{3}-6x^{2} -3)[/tex]
First we have to open the brackets.
=[tex]4x^{2} -3x+5x^{3}+6x^{2} +3[/tex]
Now we have to add the coefficients of same variable having same powers.
[tex]=5x^{3}+10x^{2} -3x+3[/tex]
Hence if M(x)=[tex]4x^{2} -3x[/tex] , N(x)=[tex]-5x^{3}-6x^{2} -3[/tex] then difference between {M(x)-N(x)} =[tex]5x^{3}+10x^{2} -3x+3[/tex].
Learn more about equations at https://brainly.com/question/2972832
#SPJ2